Factores determinantes del empleo informal en las pequeñas empresas de calzado del distrito El Porvenir. - Salazar Rodríguez, Alex Raúl (2012)
The aim of this investigation is to know which are the determinants of informal employment in small businesses Shoe District El Porvenir, for it, considering Structuralist and institutionalist theories. To obtain the information it has two moments, the first moment research is documentary and the second moment consists of fieldwork in which we used the survey to 367 total employees was calculated based on random sampling formula Simple, resulting from research, that the determinants of informal employment is the lack of labor law regime Mype this is due mainly to the lack of training in the law (79%) and the level of education with which have employees, another factor is given by the breach of the regulations due to lack of contracts (65%), and excess labor supply found in jobs that have very little job security such as the owner, assistant dresser and shoe manufacturing. Finally, the method used is the inductive-deductive, inductive method, is used to declare that law were at work in the case of informal employment and the deductive method, is used to combine these laws and get the results.